The associations between genetics, salt taste perception and salt intake in young adults. (September 2020) - Pilic, Leta; Lubasinski, Nicole Jane; Berk, Melis; Ward, Delia; Graham, Catherine Anna-Marie; Da Silva Anastacio, Viviane; King, Alexandra; Mavrommatis, Yiannis
Highlights: Variation in the TRPV1 gene is associated with perception and preference of salt. Preference for soup with high salt content is associated with higher salt intake. Salt habit is associated with preference for salt in soup. Salt habit is a driver of salt intake in young and healthy adults. Sensory appeal is important when personalising advice to reduce salt intake. Abstract: Food liking is one of the main determinants of food intake. Salt taste perception and preference, that play a role in liking of salt, may be genetically determined, although research in humans is scarce. The aim of this study was to explore the associations between genetics, salt taste perception, preference, self-reported salt habit and intake. The participants were young (18–35 years) and healthy adults (32 males and 63 females). Salt taste thresholds were determined with British Standard ISO3972:2011 methodology and salt taste preference by ratings of saltiness and pleasantness of tomato soup with salt concentrations reflecting salt content in foods. Self-reported salt habit was determined by asking participants how salty they usually eat their food and salt intake with two 24-hour 5-step multiple pass recalls. Genotyping for variants in the SCNN1B rs239345 and TRPV1 rs8065080 was performed. Participants homozygous for the minor allele of the rs8065080 had lower ratings of saltiness (p = 0.008) and higher ratings of pleasantness of soup (p = 0.027) when compared to major allele carriers. Preference for salt in soup was associated with salt habit (p = 0.003) and participants with high salt preference had higher salt intake compared to those with low salt preference (2236 ± 261 vs. 1543 ± 107 mg/1000 kcal, p = 0.017). TRPV1 rs8065080 may play a role in salt taste perception and preference, which should be confirmed in a larger sample size study. Hedonic appeal of salty food should be considered when providing personalised advice to change this behaviour.